Assessment in vitro of the antimalarial and transmission-blocking activities of cipargamin and ganaplacide in artemisinin-resistant Plasmodium falciparum - Yipsirimetee, A; Chiewpoo, P; Tripura, R; Lek, D; Day, NPJ; Dondorp, AM; Pukrittayakamee, S; White, NJ; Chotivanich, K (American Society for Microbiology, 2022)
Artemisinin resistance in Plasmodium falciparum has emerged and spread widely in the Greater Mekong Subregion, threatening current first-line artemisinin combination treatments. New antimalarial drugs are needed urgently. Cipargamin (KAE609) and ganaplacide (KAF156) are promising novel antimalarial compounds in advanced stages of development. Both compounds have potent asexual blood stage activities, inhibit P. falciparum gametocytogenesis, and reduce oocyst development in anopheline mosquitoes. In this study, we compared the asexual and sexual stage activities of cipargamin, ganaplacide, and artesunate in artemisinin-resistant P. falciparum isolates (n = 6; K13 mutations C580Y, G449A, and R539T) from Thailand and Cambodia. Asexual blood stage antimalarial activity was evaluated in a SYBR-green I-based 72-h in vitro assay, and the effects on male and female mature stage V gametocytes were assessed in the P. falciparum dual gamete formation assay. Ganaplacide had higher activities than cipargamin and artesunate, with mean (standard deviation [SD]) 50% inhibitory concentrations (IC50s) against asexual stages of 5.6 (1.2) nM and 6.9 (3.8) nM for male gametocytes and 47.5 (54.7) nM for female gametocytes. Cipargamin had a similar potency against male and female gametocytes, with mean (SD) IC50s of 115.6 (66.9) nM for male gametocytes, 104.9 (84.3) nM for female gametocytes, and 2.4 (0.7) nM for asexual stages. Both cipargamin and ganaplacide showed significant transmission-blocking activities against artemisinin-resistant P. falciparum in vitro.